Determinants of Islamic banking products selection in Sri Lanka and way forward - Mohd Imtiyaz, Mohamed Noordeen; Che Mohd Salleh, Marhanum; Abujarad, Ismael (World Academy of Islamic Management (WAIM), 2025)
The Islamic finance industry in Sri Lanka gained a considerable market share in the banking industry. Though a prominentbusiness conglomerate has been given licenses to operate as a full-fledgedIslamic bank, other institutions also operate as Islamic banking windows. A rational banking client generally considers various factors when selecting a bank for financial dealings. Attractive rate of return, hassle-free customer service and proximity areamong the priorities. Sharia compliance factor is the utmostimportant factor for Islamic banking clients. Strong Presence of conventional banks and a population-wise smaller Muslim customer base, Islamic banks still face challenges in attracting new customers to sell their shari'a-basedproducts. Thus, this study investigated why the only Islamic bank inthe country is unable to attract more customers for their services. Also, this study attempted to find strategies for Islamic financial institutions to increase their market share local market and globally. The Theory of Reason Action (TRA) is used to develop the theoretical framework of the study. To achieve the objectives of the study, primary data has beencollectedthrough a surveyof 124 respondents in Sri Lanka. Convergent and divergent validity was proved through Confirmatory factor analysis. Structural Equation Modelling results indicate that customer selection of Islamic Banking products is positively influencedby product awareness, availability of branches and rate of return. The results provided by the study would give some ideas to the bankers on how to attract more customers for future sustainability. This includes to enhance customer awareness towards Islamic banking products. This wouldalso assist the other stakeholders and prospective investors to join the Islamic banking industry in future.